Răspuns :
a) 13^(6-5)=13^1=13
b) 23^(7-2-1)=23^4
c) 2^(15-10)=2^5
d)11^5-11^5=0
e) (3^6*5^3):(3^6*5^3)=1
f) 2^(24-23)+3^(30-29)=2^1+3^1=5
g) 3^(1+2+3+200):3^(2*103)=3^206:3^206=1
b) 23^(7-2-1)=23^4
c) 2^(15-10)=2^5
d)11^5-11^5=0
e) (3^6*5^3):(3^6*5^3)=1
f) 2^(24-23)+3^(30-29)=2^1+3^1=5
g) 3^(1+2+3+200):3^(2*103)=3^206:3^206=1
13^6:13^5=13^(6-5)=13^1=13
23^7:23^2:23=23^(7-2-1)=23^4
(2^3)^5:2^10=2^15:2^10=2^(15-10)=2^5
11^50:11^45-11^5=11^(50-45)-11^5=11^5-11^5=0
(3^2*5)^3:(3^6*5^3)=3^6*5^3:3^6*5^3=1
4^12:2^23+9^15:3^29=(2^2)^12:2^23+(3^2)15:3^29=2^24:2^23=3^30:3^29=2+3=5
(3*3^2*3^3*3^200):9^103
3^(1+2+3+200):(3^2)^103=3^206:3^206=3^(206-206)=3^0=1
23^7:23^2:23=23^(7-2-1)=23^4
(2^3)^5:2^10=2^15:2^10=2^(15-10)=2^5
11^50:11^45-11^5=11^(50-45)-11^5=11^5-11^5=0
(3^2*5)^3:(3^6*5^3)=3^6*5^3:3^6*5^3=1
4^12:2^23+9^15:3^29=(2^2)^12:2^23+(3^2)15:3^29=2^24:2^23=3^30:3^29=2+3=5
(3*3^2*3^3*3^200):9^103
3^(1+2+3+200):(3^2)^103=3^206:3^206=3^(206-206)=3^0=1